Attentional Bias Modification Facilitates Attentional Control Mechanisms: Evidence from Eye Tracking - Chen, N.; Clarke, Patrick; Watson, T.; MacLeod, C.; Guastella, A. (Elsevier BV, 2015)
Social anxiety is thought to be maintained by biased attentional processing towards threatening information. Research has further shown that the experimental attenuation of this bias, through the implementation of attentional bias modification (ABM), may serve to reduce social anxiety vulnerability. However, the mechanisms underlying ABM remain unclear. The present study examined whether inhibitory attentional control was associated with ABM. A non-clinical sample of participants was randomly assigned to receive either ABM or a placebo task. To assess pre–post changes in attentional control, participants were additionally administered an emotional antisaccade task. ABM participants exhibited a subsequent shift in attentional bias away from threat as expected. ABM participants further showed a subsequent decrease in antisaccade cost, indicating a general facilitation of inhibitory attentional control. Mediational analysis revealed that the shift in attentional bias following ABM was independent to the change in attentional control. The findings suggest that the mechanisms of ABM are multifaceted.